The Day of the Lord in Amos 5:18-20: A Critical Interpretation and Its Relevand to Social Justice In Indonesian and India Context - Jelfy L Hursepuny; K Chongloi (Program Pascasarjana UKIM, 2025)
People always imagine “the day of the Lord” as matters that have relation with the second coming of Jesus Christ, a day of judgment, and the future. But, the concept of the day Lord as witnesses in the book of Amos is always related to the present time of Amos, not the future, as we had been imagining before. The purpose of this article is to examine the meaning of Amos 5:18-20 using the critical historical interpretation. The result shows us that the meaning of the day of the Lord in Amos 5:18-20 is about the social justice renewal in society. This spirit of Amos’s prophecies enables Christians, the church, and society to understand social justice renewal as the call of faith that must be continuously internalised and practised.